From back alley to the border : criminal abortion in California, 1920-1969 - Gutierrez-Romine, Alicia (University of Nebraska Press, 2020)
"'From Back Alley to the Border' examines the history of illegal abortion in California and the role that abortion providers played in exposing and exploiting the faults in California's anti-abortion statute throughout the twentieth century"--